RELATIONSHIP OF FAMILY KNOWLEDGE TODRINKING COMPLIANCE MEDICINE FOR FAMILY MEMBERS WITH HYPERTENSIONAT THE SEROJA PUBLIC HEALTH CENTER IN BEKASI - Lola Rikzy; Ani Anggraini; Dinda Nur Fajri (Jurnal Medicare, 2024)
Background: Hypertension is a big and serious problem because it is often not detected even though it has been for years. Hypertension can be defined as persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. When symptoms arise, hypertension has become a disease that must be treated for life, the trearted that must be issued is quite expensive and takes a long time. Research Objectives To find out whether there is family knowledge on medication adherence and blood pressure in patients with hypertension at the Seroja Health Center, Bekasi City. Research Methods : The research design used is a quantitative research type, the research design is analytic with a cross sectional approach. Sampling using stratified random sampling as many as 199 people. Metods of data collection using a questionnaire. The statistical test uses an alternative test, namely the Fisher’s test. Research Results: Based on the results of statistical analysis using the Chi Square test obtained p-value 0.000, it can be concluded that P-Value (0.000) < (0.05) which means that there is a relationship between family knowledge and adherence to taking medication with hypertension at the Seroja Health Center in Bekasi City.  Conclusion: There is a relationship between family knowledge on medication adherence and hypertension at the Seroja Public Health Center in Bekasi City.